Mitochondrial NHE1: a newly identified target to prevent heart disease - ALVAREZ, BERNARDO V.; Villa Abrille, María C. (Frontiers in Physiology, 2013)
Mitochondrial damage has been associated with early steps of cardiac dysfunction in heart subjected to ischemic stress, oxidative stress and hypertrophy. A common feature for the mitochondrial deterioration is the loss of the mitochondrial membrane potential (ΔΨm) with the concomitant irreversible opening of the mitochondrial permeability transition pore (MPTP) which follows the mitochondrial Ca2+ overload, and the subsequent mitochondrial swelling. We have recently characterized the expression of the NHE1 Na+/H+ exchanger (NHE1m) in mitochondrial membranes. This surprising observation provided a unique target for the prevention of the Ca2+-induced MPTP opening, based on the inhibition of the NHE1m. In this line, inhibition of NHE1m activity and/or reduction of NHE1m expression, decreased the Ca2+-induced mitochondrial swelling and the release of reactive oxygen species in isolated cardiac mitochondria, and preserved the ΔΨm in isolated cardiomyocytes. Mitochondrial NHE1 thus represents a novel target to prevent cardiac disease, opening new avenues for future research.